Breaking Barriers Exploring Guardianship & Public Administration Challenges Facing Egyptian Widows - Maher, Caroline (AUC Knowledge Fountain, 2025)
This thesis examines the influence of guardianship policies and the administrative infrastructure on the well-being of widows' families in Egypt. Widows in Egypt encounter significant challenges in exercising their guardianship rights due to patriarchal norms, bureaucratic hurdles, inefficient systems, and limited access to information. These obstacles can negatively impact their children's well-being, as well as economic and social stability. Despite social media activism, calls for administrative reforms, and legislative debates, no changes have occurred. This study aims to conduct in-depth exploratory qualitative research to analyze the challenges and limitations of current guardianship policies and administrative systems affecting widows’ families in Egypt. Additionally, it seeks to pave the way for developing effective policy reforms.